Branched perfluorohexanesulfonic acid (PFHxS) and perfluoroheptanoic acid (PFHpA): ’Safer’ per- and polyfluoroalkyl substances (PFASs) alternatives for their effects on gut microbiota and metabolic function in children - Zhen Hong; Lizi Lin; Haoran Yu; Qinzhi Wei; Yunting Zhang; Wanting He; Xuemei Liao; Jin Jing; Guanghui Dong; Zheqing Zhang (Environment International)
This study examined the effects of branched perfluorohexanesulfonic acid (PFHxS) and perfluoroheptanoic acid (PFHpA), two alternatives to per- and polyfluoroalkyl substances (PFASs), on gut microbiota and metabolic function in Chinese children aged 6–9 years. A total of 336 children were enrolled, providing plasma and fecal samples. Gut microbiota composition was assessed through 16S rRNA gene sequencing, and fecal metabolites and short-chain fatty acids (SCFAs) were analyzed using targeted metabolomics profiling and high-performance liquid chromatography (HPLC), respectively. PFASs in plasma samples were detected using ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS). The results revealed that exposure to PFHpA significantly reduced microbial diversity and richness in the gut microbiota. Specific bacterial genera were found to be positively or negatively associated with branched PFHxS and PFHpA exposures (β = –0.008–––0.009, P_fdr = <0.001–––0.048), with Parabacteroides positively correlated with branched PFHxS and Lachnospiraceae FCS020 group negatively correlated with PFHpA. Metabolomic analysis showed that branched PFHxS and PFHpA exposures were associated with distinct changes in fecal metabolite profiles (β = –0.182–––0.177, P_fdr = 0.015–––0.172), particularly reducing fatty acids and amino acids. Additionally, higher exposure to PFHpA was linked to a reduction in SCFA profiles, such as valeric acid (β = –0.691 − –0.341, P = 0.011–––0.030). This study offers new insights into the potential adverse effects of PFASs alternatives, specifically branched PFHxS and PFHpA, on the gut microbiome and metabolic health in children.